2021
DOI: 10.21037/tlcr-21-501
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of afatinib as first-line therapy for advanced EGFR mutation-positive non-small cell lung cancer in Korea

Abstract: Background: We investigated the clinical characteristics and treatment outcomes of Korean patients receiving first-line afatinib for advanced epidermal growth factor receptor mutation-positive (EGFRm + ) nonsmall cell lung cancer (NSCLC) in a real-world setting.Methods: Electronic case reports were retrospectively reviewed from patients across 15 sites in South Korea. Outcome measures included baseline characteristics, overall response rate (ORR), time-totreatment discontinuation (TTD), and overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 45 publications
6
22
0
Order By: Relevance
“…A retrospective multicenter study also showed that afatinib was effective in patients with compound mutations (median time of treatment: 12.3 months, 95% CI: 7.7–17.0 months; median OS: 29.1 months, 95% CI: 20.4–37.7 months) and in patients with major uncommon mutations (G719X and L861Q) (median time of treatment: 20.3 months, 95% CI: 15.1–25.5 months; median OS: 30.6 months, 95% CI: 26.3–34.8 months), but not in patients harboring drug-resistant mutations (ex20ins, S768I, T790M) (median time of treatment: 3.8 months, 95% CI: 1.7–6.0 months; median OS: 8.5 months, 95% CI: 5.2–11.7 months) [23] . In addition, real-world data showed that afatinib reached an ORR of 100% in four patients with advanced NSCLC with exon 18 and 21 mutations [24] . Tan et al [25] retrospectively found that afatinib was superior to gefitinib/erlotinib/icotinib for patients with advanced or recurrent NSCLC with atypical plus typical mutations (ORR: 100.0% vs .…”
Section: Egfr Compound Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective multicenter study also showed that afatinib was effective in patients with compound mutations (median time of treatment: 12.3 months, 95% CI: 7.7–17.0 months; median OS: 29.1 months, 95% CI: 20.4–37.7 months) and in patients with major uncommon mutations (G719X and L861Q) (median time of treatment: 20.3 months, 95% CI: 15.1–25.5 months; median OS: 30.6 months, 95% CI: 26.3–34.8 months), but not in patients harboring drug-resistant mutations (ex20ins, S768I, T790M) (median time of treatment: 3.8 months, 95% CI: 1.7–6.0 months; median OS: 8.5 months, 95% CI: 5.2–11.7 months) [23] . In addition, real-world data showed that afatinib reached an ORR of 100% in four patients with advanced NSCLC with exon 18 and 21 mutations [24] . Tan et al [25] retrospectively found that afatinib was superior to gefitinib/erlotinib/icotinib for patients with advanced or recurrent NSCLC with atypical plus typical mutations (ORR: 100.0% vs .…”
Section: Egfr Compound Mutationsmentioning
confidence: 99%
“…[23] In addition, real-world data showed that afatinib reached an ORR of 100% in four patients with advanced NSCLC with exon 18 and 21 mutations. [24] Tan et al [25] retrospectively found that afatinib was superior to gefitinib/erlotinib/icotinib for patients with advanced or recurrent NSCLC with atypical plus typical mutations (ORR: 100.0% vs. 54.5%, P = 0.02; median PFS: not reached vs. 13.6 months, P = 0.03). These results indicated that afatinib could reduce heterogeneity and have a more extensive inhibitory profile than firstor thirdgeneration TKIs, which supports afatinib as a treatment option for EGFR compound mutations.…”
Section: Egfr Compound Mutationsmentioning
confidence: 99%
“…CANCER RESEARCH AND TREATMENT (CRT) 5 Korean Cancer Association This article is protected by copyright. All rights reserved.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Afatinib is a second-generation, irreversible EGFR-TKI, and its good CNS efficacy has been previously shown in several studies, where it was also superior to first-G EGFR-TKIs for brain metastasis [4,5,11]. Until now, however, the role of brain RT for baseline brain metastasis before afatinib therapy has not been evaluated.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation